Faktor Fisik Lingkungan dan Perilaku Merokok sebagai Prediktor Sick Building Syndrome Pada Pegawai di Kantor Dinas Kesehatan Provinsi Kalimantan Timur - Syafira Fitri; Vivi Filia Elvira; Dewi Novita Hardianti; Ayudhia Rachmawati; Masithah Masithah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2026)
Sick Building Syndrome (SBS) is a group of health complaints caused by poor indoor air quality and commonly affects office workers. This study aimed to analyze the effect of humidity, lighting intensity, PM₁₀ concentration, and smoking behavior on SBS symptoms among employees of the East Kalimantan Provincial Health Office. This research was conducted in 2025 using an analytic observational design with a cross-sectional approach. The population consisted of 128 employees selected using total sampling. Data were collected through direct measurement using hygrometer, lux meter, and particulate matter monitor, along with structured questionnaires for SBS symptoms and smoking behavior. The questionnaire was adapted from the US EPA BASE Study instrument (US EPA, 1998) with adequate validity and reliability (Cronbach's alpha >0.7). Data were analyzed using univariate, chi-square test, and binary logistic regression. The results showed that 52.3% of respondents experienced SBS symptoms. PM₁₀ concentration significantly affected SBS occurrence (p = 0.029; OR = 3.263; 95% CI = 1.131–9.418), while humidity, lighting intensity, and smoking behavior were not significant. PM₁₀ was identified as the dominant factor influencing SBS. Priority interventions including HEPA filter installation, 5R K3 program, and intensive cleaning are recommended to reduce PM₁₀ concentration and lower the risk of SBS in office environments.